The Influence of Principal Academic Supervision and Teacher Competence on the Quality of Education in Public Junior High Schools in Doloksanggul District - Simamora, Marlina; Sitio, Robert Juni Tua; Pakpahan, Betty A. S.; Panjaitan, Binur; Marbun, Rencan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Variables This study aims to determine the effect of Principal Academic Supervision and Teacher Competence individually or together on the Quality of Education, with the hypothesis that there is a positive and significant effect between Principal Academic Supervision and Teacher Competence. This study uses a descriptive quantitative method. The population of the study was all junior high school teachers in Doloksanggul District, totaling 176 people with a sample of 125 people. The research instrument was a closed questionnaire, which was compiled by the researcher based on the research variable indicators. The questionnaire trial was conducted on 30 teachers outside the research sample, and has been tested with validity and reliability tests. The results of the study show that: 1). There is a positive effect between Principal Academic Supervision on the Quality of Education obtained from tcount>ttable, namely 5.680>1.980, with a large influence of 42%, and there is a significant effect obtained from Y ̂ = 19.929 + 0.680X_1. 2). There is an influence between Teacher Competence on the Quality of Education of 40.1% with tcount>ttable, namely 5.233>1.980, 3). There is a positive and significant influence between the Principal's Academic Supervision and Teacher Competence together on the Quality of Education of 52.6% with Fcount>Ftable, namely 67.827>3.00, thus H0 is rejected and Ha is accepted.